Non-pharmacological interventions on cognitive functions in older people with mild cognitive impairment (MCI) - Ligo Teixeira, Camila Vieira [UNESP]; Bucken Gobbi, Lilian Teresa [UNESP]; Corazza, Danilla Icassatti [UNESP]; Stella, Florindo [UNESP]; Riani Costa, Jose Luiz [UNESP]; Gobbi, Sebastiao [UNESP] (Elsevier B.V., 2012)
Mild cognitive impairment (MCI) can be a stage of pre-dementia. There is no consensus about pharmacological treatment for this population, so it is important to structure non-pharmacological interventions for increasing their cognitive reserve. We intended to analyze the effects of non-pharmacological interventions in the cognitive functions in older people with MC, in form of a systemic review. Data sources were the Web of Science, Biological Abstracts, Medline, Pub Med, EBSCHost, Scirus and Google Scholar. All studies were longitudinal trials, with MCI sample, aged > 60 years, community-dwelling, and having cognitive functions as dependent variable. Seven studies, from 91 previously selected ones, were identified according to the inclusion criteria. Six studies used cognitive intervention, improving memory and one study used physical activity as intervention, improving executive functions. The results show evidence that physical activity and cognitive exercise may improve memory and executive functions in older people with MCI. But yet, more controlled studies are needed to establish a protocol of recommendations regarding the systemization of exercise, necessary to produce benefits in the cognitive functioning in older people with MCI. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Mild cognitive impairment; Cognitive functions; Physical activity; Cognitive intervention; Systemic review